A behavioral theory of patent application rhythm: The moderating roles of CEO overconfidence and discretion. Issue 4 (27th August 2019) - Guo, Bin; Ding, Peng
Abstract : Purpose: Previous studies employing the behavioral theory of the firm have not explicitly taken the roles of decision makers and corporate governance into consideration. The purpose of this paper is to fill in this gap by integrating CEO overconfidence and discretion into the performance feedback mechanism. Design/methodology/approach: Financial data were collected from 1, 730 Chinese listed companies in the period 2011–2015. Firm-level patent application data were collected for 1988–2015 to measure firm patent application rhythm. Hypothesis testing relied on the fixed effect panel data model. Findings: There is a positive relationship between performance discrepancy and a firm's patent application rhythm. CEO overconfidence will weaken this positive relationship. The negative moderating effect of CEO overconfidence will be less pronounced when CEO discretion is high. Originality/value: To the best of the authors' knowledge, this work is the first empirical study that investigates the roles of CEO overconfidence and discretion in shaping the performance feedback mechanism.